The Currency Exposure and Syariah Compliant Status under Different Time Domains: Insights from Maximal Overlap Discrete Wavelet Transformation (MODWT) Analysis - Hishamuddin Abdul Wahab; Wan Nur Rahini Aznie Zainudin; Sharifah Fairuz Syed Mohamad; Asmah Mohd. Jaapar (Horizon Research Publishing, 2024)
Indexed by Scopus